2019
DOI: 10.3390/cells8010064
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine Prevents Aβ-Induced Oxidative Stress and Inflammation in Microglial Cells: A Key Role of TGF-β1

Abstract: Carnosine (β-alanyl-L-histidine), a dipeptide, is an endogenous antioxidant widely distributed in excitable tissues like muscles and the brain. Carnosine is involved in cellular defense mechanisms against oxidative stress, including the inhibition of amyloid-beta (Aβ) aggregation and the scavenging of reactive species. Microglia play a central role in the pathogenesis of Alzheimer’s disease, promoting neuroinflammation through the secretion of inflammatory mediators and free radicals. However, the effects of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 103 publications
(123 reference statements)
5
89
0
Order By: Relevance
“…Furthermore, strong evidence that carnosine protects against pathologies characterized by oxidative stress and/or inflammation such as diabetes [29], depression [30], cerebral ischemia [31] and Alzheimer's disease (AD) [32] has been proved. In previous studies, we showed that 20 mM carnosine is highly effective to positively regulating macrophage and microglial functions [23,33]. In particular, we found that carnosine, in macrophages challenged with LPS + IFN-γ, increases the rate of NO transformation into its stable end-product nitrite, modulates the composition of macrophage sub-populations and decreases the release of pro-inflammatory cytokines into the cell medium.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, strong evidence that carnosine protects against pathologies characterized by oxidative stress and/or inflammation such as diabetes [29], depression [30], cerebral ischemia [31] and Alzheimer's disease (AD) [32] has been proved. In previous studies, we showed that 20 mM carnosine is highly effective to positively regulating macrophage and microglial functions [23,33]. In particular, we found that carnosine, in macrophages challenged with LPS + IFN-γ, increases the rate of NO transformation into its stable end-product nitrite, modulates the composition of macrophage sub-populations and decreases the release of pro-inflammatory cytokines into the cell medium.…”
mentioning
confidence: 76%
“…Additionally, a significant deficit of TGF-β1, paralleling memory deficits and depressive-like phenotype, has been found in the hippocampus of Aβ-injected mice [89]. Very recently, the ability of carnosine to protect brain macrophages and neurons against Aβ-induced cell toxicity by increasing TGF-β1 expression and secretion has been proposed [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ, amyloid beta; Aβ 1−42 , 42-amino acid-long amyloid beta peptide; BDNF, brain-derived neurotrophic factor; IL-1β, interleukin-1 beta; MMP-9, metalloprotease-9; NGF, nerve growth factor; mNGF, mature nerve growth factor; proNGF, precursor of the nerve growth factor; RNS, reactive nitrogen species; ROS, reactive oxygen species; TGF-β, transforming growth factor-beta; TNF-α, tumor necrosis factor-alpha. produce and release proinflammatory cytokines (14,68) and also by interfering with the synthesis of anti-inflammatory cytokines, for instance the transforming growth factor-beta 1 (TGF-β1) ( Figure 2) (69)(70)(71). This early proinflammatory process is characterized by neuronal and microglia-derived cytokines and chemokines as well as by mobilization of microglia toward Aβ-burdened neurons (Figure 2) (19,72).…”
Section: The Role Of Microgliamentioning
confidence: 99%
“…Corona et al have demonstrated that carnosine supplementation inhibited AβP deposition and improved learning abilities of AD model mice [90]. Carnosine prevents the oxidative stress and inflammation induced by AβP [91]. We showed that carnosine attenuated the neuronal death induced by prion protein fragment peptide (PrP106-126) by changing its conformation [92].…”
Section: Carnosine As An Endogenous Neuroprotectormentioning
confidence: 73%